Safety citizenship behavior (SCB) in the workplace: A stable construct? Analysis of psychometric invariance across four European countries. (August 2019) - Curcuruto, Matteo; Conchie, Stacey M.; Griffin, Mark A.
Highlights: Safety citizenship behavior (SCB) is a multidimensional construct. Affiliative vs challenging citizenship refer to two superordinate typologies of SCB. The superordinate factor structure of SCB is tested across four European samples. Results support equivalence of configuration, loadings, variances and covariances. Abstract: Safety citizenship behaviors (SCBs) are important participative organizational behaviors that emerge in work-groups. SCBs create a work environment that supports individual and team safety, encourages a proactive management of workplace safety, and ultimately, prevents accidents. In spite of the importance of SCBs, little consensus exists on research issues like the dimensionality of safety citizenship, and if any superordinate factor level of safety citizenship should be conceptualized, and thus measured. The present study addressed this issue by examining the dimensionality of SCBs, as they relate to behaviors of helping, stewardship, civic virtue, whistleblowing, voice, and initiating change in current practices. Data on SCBs were collected from four industrial plants (N = 1065) in four European countries (Italy, Russia, Switzerland, United Kingdom). The results show that SCBs structure around two superordinate second-order factors that reflect affiliation and challenge. Multi-group analyses supported the structure and metric invariance of the two-factor model across the four national subsamples.